Determinants of physical activity habit formation: a theory-based qualitative study among young adults - Rinat Avraham; Tzahit Simon-Tuval; Dina Van Dijk (International Journal of Qualitative Studies on Health & Well-Being)
Purpose Engagement in physical activity significantly contributes to reducing the onset and severity of chronic diseases. Nonetheless, establishing habits around this behaviour remains a persistent challenge. This research endeavours to discern the determinants influencing the formation of physical activity habit among young adults in Israel, drawing upon a socio-ecological model. Methods A qualitative approach with phenomenological-hermeneutical method was used. In-depth interviews were carried to cover four levels of the socio-ecological model. Results Interviewees were categorized into three subgroups according to their physical activity habit strength: Habitually physically active (n = 8), Variably physically active (n = 11), and physically inactive (n = 6). The content analysis yielded four overarching themes associated with physical activity habit formation. Intrapersonal determinants encompassed personal traits, perceptions and attitudes, perceived benefits, and emotional responses related to physical activity. Interpersonal determinants encompassed social support, modelling support, and peer pressure. Community determinants pertained to social norms, resource availability, and accessibility. Finally, public policy considerations encompassed educational policies as well as workplace policies and cultural influences. Conclusions This study highlights the unique determinants contributing to the formation of physical activity habit. As intrapersonal and interpersonal factors are significant determinants, interventions should focus on these elements in order to promote this behaviour among young adults.